Heavy probes in strongly coupled plasmas with chemical potential - Samberg, Andreas; Ewerz, Carlo (1st Karl Schwarzschild Meeting on Gravitational Physics, 2015)
We study the properties of heavy probes moving in strongly coupled plasmas at finite chemical potential. Using the gauge/gravity duality we consider large classes of gravity models consisting in deformed AdS55_{\!5} spacetimes endowed with Reissner-Nordström-type black holes. We report on our analysis of the screening distance of a quark-antiquark pair, its free energy, and the running coupling. These observables show a certain insensitivity as to which model and deformation is used, pointing to strong-coupling universal behavior. Thus, the results may be relevant for modeling heavy quarkonia traversing a quark-gluon plasma at finite net baryon density, and their suppression by melting.
Gesehen am 19.02.2018